Radical Female Authorship: Towards a psycho-feminist literary criticism - Marín Calderón, Norman David (2006)
In this article, and from the reflections of Sandra Gilbert and Susan Gubar, I will start the study of traditional concepts of authorship, women's writing, and the textual/sexual meaning of authorship. Likewise, I will analyze the conceptualization of desire in the formation of gender identity, subject formation, and female representation according to the theory of psychoanalyst Jacques Lacan and the rereading of his theories by feminist psychoanalysis. Next, the issue of epistolary writing will be examined as a confessional and subversive kind of female writing, mainly from the perspective of Linda Kauffman. Finally, I will examine the subversive elements of sisterhood and female sexuality according to the radical ideas of bell hooks and Adrienne Rich.